Viewing D&E Abortion Procedure Promotes Negative Emotions - Anna Cecilia Gessler; Dominic Zak; Isabella Dammeyer; Peter Patelli; Rachel Vander Woude; Cole Stull; Rylie Severson; Derek Doroski (Issues in Law & Medicine, 2026)
Induced abortion, “an intervention intended to terminate a pregnancy so that it does not result in a live birth”, is a highly contentious procedure, with varying comprehension of actual abortion procedures used. The comprehension of the actual abortion procedure used in the second trimester may affect the various levels of support or lack thereof for abortion after the first trimester. The most common second trimester surgical abortion procedure is Dilation and Evacuation (D&E). Many commonly available descriptions of the D&E lack sufficient detail and may not be sufficient for patients or the public to understand the procedure. Little is known about the public’s understanding of D&E abortion procedures. This pilot study investigates how viewing an animated D&E procedure impacts participants’ perceived understanding of the procedure, emotional responses, and pro-life/prochoice affiliations. Researchers conducted a 14-item pre- and post- intervention survey in the Ohio Valley region (n=50). While participants’ pro-life/pro-choice position on abortion did not immediately change after watching the video, participants’ perceived understanding of the procedure increased (p